Existence of non-negative solutions for semilinear elliptic systems via variational methods - Khademloo, Somayeh; Heidarkhani, Shapur (Nonlinear Analysis: Modelling and Control, 2012)
In this paper we consider a semilinear elliptic system with nonlinearities, indefinite weight functions and critical growth terms in bounded domains. The existence result of nontrivial nonnegative solutions is obtained by variational methods.